Polemika na temat przydatności podziału na czynności kauzalne i abstrakcyjne – wybrane zagadnienia - Nowakowski, Tobiasz (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The author has presented different conception of dualistic divide on causation and non-causation legal actions. The analyses focuses on need to abandon that dualistic divide. The main argument is ambiguity word of causae. Author’s view is based on polish conventional legal actions theory. It professes that each legal action has got constructional and consequential principles, which are sufficient to describe consideration of them.